Advertising during COVID-19: Exploring Perceived Brand Message Authenticity and Potential Psychological Reactance. Issue 3 (21st July 2021) - Shoenberger, Heather; Kim, Eunjin (Anna); Sun, Yuan
Abstract: This study seeks to examine under what circumstances brand advertising that advocated for socially desirable behaviors (e.g., mask wearing) during the COVID-19 pandemic may be successful in increasing the intention to engage in such behaviors. In doing so, we examine the effectiveness of real brands' persuasive attempts via activist advertising, focusing on messages used in real advertisements that may cause psychological reactance. Using a 2 (message type: threat to freedom vs. no threat) × 2 (brand: Uber vs. Heineken) between-subjects design, our study confirms that threat to freedom messages lead to lower ad attitudes, lower intention to engage in socially responsible behaviors, and greater psychological reactance. Brands should be careful when using "threat to freedom" language in their advertising. Further, our results suggest that perceived authenticity of a brand's messaging is key to the success of activist advertising.